Role of Glycine max in improving drought tolerance in Zanthoxylum bungeanum - Li, Zilong (2020)
Intercropping may improve community stability and yield under climate change. Here, we set up a field experiment to evaluate the advantages of cultivating Z anthoxylum bungeanum with Capsicum annum, and Z. bungeanum with Glycine max as intercrops, compared with cultivating Z. bungeanum in monoculture. Effects of extreme drought stress conditions on morphological, physiological, and biochemical traits of the three crop species cultivated in the three contrasting planting systems were compared. Results showed that extreme drought conditions induced negative impacts on Z. bungeanum grown in monoculture, due to reduced growth and metabolic impairment. However, limited stomatal conductance, reduced transpiration rate (Tr), and increased water use efficiency, carotenoid content, catalase activity, and accumulation of soluble sugars in Z. bungeanum indicated its adaptive strategies for tolerance of extreme drought stress conditions. Compared with cultivation in monoculture, intercropping with C. annum had positive effects on Z. bungeanum under extreme drought stress conditions, as a result of improved crown diameter, leaf relative water content (LRWC), net photosynthetic rate, and proline content, while intercropping with G. max under extreme drought stress conditions increased net CO2 assimilation rates, LRWC, Tr , and superoxide dismutase (SOD) activity. In conclusion, Z. bungeanum has an effective defense mechanism for extreme drought stress tolerance. Intercropping with G. max enhanced this tolerance potential primarily through its physio-biochemical adjustments, rather than as a result of nitrogen fixation by G. max.